Features of the Natural Environment as a Determinant of the Development of Rural Tourism in the Region of Wielkopolska - Kałowska, Joanna; Poczta-Wajda, Agnieszka (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2008)
Rural areas constitute a valuable environment and offer proper conditions for the development of tourism. The intensifying tendency towards tourist trips to rural areas with attractive natural environment can be linked to the popularization of the idea of sustainable development and, consequently, to the growing pro-environmental awareness of the world's communities. The rural recreational space and its landscape attractiveness exert a strong influence on the development of agri-tourism. The authors of the article attempt to identify the attractive features of the landscape of the Wielkopolska region and to classify and assess the types of rural areas existing in Wielkopolska from the point of view of opportunities they offer for the development of tourism. The research covered the qualities of the landscape of the Wielkopolska region, analysed in accordance with its division into 31 administrative districts (poviats), and took into account some measurable factors: legally protected areas of especially great natural value (shown as a percent of the total area), the share of woodland (in the total area), the share of lakes, (in the total area), the share of meadows and pasture-land in the total area of arable land (in %), the number of monuments of nature per 1 km2. The following methods were used to conduct the research: multidimensional grouping in accordance with Ward's method, valorisation of groups with the help of a synthetic measure and linear regression of numerous variables. The conducted analyses have indicated that the northern parts of the Wielkopolska region have a larger potential for the development of tourism than its other parts. On the other hand, factors decisive for the number of farms engaging in agri-tourism are: the proportion of lakes, the proportion of forests and the number of monuments of nature per 1 km2.
Keywords: landscape attractiveness; rural tourism